Clinical analysis and treatment of symptomatic intracranial hemorrhage after deep brain stimulation surgery. (4th March 2017) - Wang, Xin; Wang, Jing; Zhao, Haikang; Li, Nan; Ge, Shunnan; Chen, Lei; Li, Jiaming; Jing, Jiangpeng; Su, Mingming; Zheng, Zhaohui; Zhang, Jinan; Gao, Guodong; et al.
Abstract: Background: Symptomatic intracranial hemorrhage (ICH) may lead to permanent neurological disability of patients and has impeded the extensive clinical application of deep brain stimulation (DBS). The present study was conducted to discuss the incidence, prevention, and treatment of symptomatic ICH after DBS surgery. Methods: From January 2009 to December 2014, 396 patients underwent DBS with a total of 691 implanted leads. In all, 10 patients had symptomatic ICH. We analyzed these cases' clinical characteristics, including comorbid diagnoses and coagulation profile. We described the onset of ICH, imaging features, clinical manifestations, treatment, neurological impairment, and outcome of DBS. Results: Of the 10 patients with symptomatic ICH, 2 had hypertension. Three cases of ICH occurred within 12 h of the procedure; four cases within 24 h. Five experienced grand mal seizures concurrently with hemorrhage. Unilateral frontal lobe hemorrhage occurred in all cases. In seven cases, hematomas occurred around the electrodes. Some hematomas were not well-circumscribed and had perihematomal edema. Conservative therapy was administered to 8 patients, and 2 patients underwent craniotomy and hematoma evacuation. All electrodes were successfully preserved. Neurological dysfunction in all patients gradually improved. Nine patients ultimately experienced effective symptom relief of Parkinson's disease with DBS. Conclusions: Symptomatic ICH should be identified as soon as possible after implantation surgery and treated effectively to limit neurological deficit and preserve DBS leads.